Risk analysis in the critical pigmeat control points - Ancuţa Marin (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
The pig meat is of particular importance in human food due to the high content of vitamins and minerals. To prevent the hazard of microbial contamination, physical contamination, chemical contamination, etc., before slaughtering and during slaughter of animals has been developed and implemented the system Hazard Analysis by Critical Control Points (HACCP).
Keywords: 330; pork meat; HACCP; organoleptic indices; contamination hazard